Pengaruh Karakteristik Fraud Pentagon Dalam Mendeteksi Kecurangan Laporan Keuangan Pada Perusahaan Sektor Keuangan Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2020 - Bambang Catur Pambudi; S. Sudrajat; Yunia Amelia (BULLET : Jurnal Multidisiplin Ilmu, 2023)
This study aims to analyze the influence of characteristicsfraud pentagon in indicating acts of fraudulent financial reporting in 27 Indonesian financial sector companies from 2016 to 2020. This study uses five independent variables in the form ofExternal Pressure, External Audit Quality,Change in Auditor, Change of Directors, andDualism Position as an indicatorfraud pentagon with the dependent variable of financial statement fraud. This study uses multiple linear regression analysis method. The results of the analysis obtained thatExternal Pressure, Change in Auditor, and Director Change has a positive effect on fraudulent financial reporting. However, External Audit Quality and Positional Dualism do not affect such reporting fraud.